Prove that $ an(2 heta) = frac{2 an( heta)}{1 - an^2( heta)} $ using the unit circle
Answer 1
Consider a point on the unit circle at an angle $ \theta $. Using the double-angle identities, we can write:
$ \sin(2\theta) = 2\sin(\theta)\cos(\theta) $
and
$ \cos(2\theta) = \cos^2(\theta) – \sin^2(\theta) $
Thus,
$ \tan(2\theta) = \frac{\sin(2\theta)}{\cos(2\theta)} = \frac{2\sin(\theta)\cos(\theta)}{\cos^2(\theta) – \sin^2(\theta)} $
Using the fact that $ \tan(\theta) = \frac{\sin(\theta)}{\cos(\theta)} $, let
$ t = \tan(\theta) $
Then
$ \sin(\theta) = \frac{t}{\sqrt{1 + t^2}} $
and
$ \cos(\theta) = \frac{1}{\sqrt{1 + t^2}} $
Substituting these into the double-angle formula gives:
$ \tan(2\theta) = \frac{2 \cdot \frac{t}{\sqrt{1 + t^2}} \cdot \frac{1}{\sqrt{1 + t^2}}}{\left(\frac{1}{\sqrt{1 + t^2}}\right)^2 – \left(\frac{t}{\sqrt{1 + t^2}}\right)^2} $
Which simplifies to:
$ \tan(2\theta) = \frac{2t}{1 – t^2} $
Answer 2
We start by using the double-angle identities for sine and cosine:
$ sin(2 heta) = 2sin( heta)cos( heta) $
and
$ cos(2 heta) = cos^2( heta) – sin^2( heta) $
Thus,
$ an(2 heta) = frac{sin(2 heta)}{cos(2 heta)} = frac{2sin( heta)cos( heta)}{cos^2( heta) – sin^2( heta)} $
Let $ t = an( heta) $, so
$ sin( heta) = frac{t}{sqrt{1 + t^2}} $
and
$ cos( heta) = frac{1}{sqrt{1 + t^2}} $
Substituting these into the double-angle formula, we get:
$ an(2 heta) = frac{2 cdot frac{t}{sqrt{1 + t^2}} cdot frac{1}{sqrt{1 + t^2}}}{left(frac{1}{sqrt{1 + t^2}}
ight)^2 – left(frac{t}{sqrt{1 + t^2}}
ight)^2} $
Simplifying, we find:
$ an(2 heta) = frac{2t}{1 – t^2} $
Answer 3
Start with the double
Start Using PopAi Today